2008
DOI: 10.1159/000160219
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of an Epignathus Associated with a 49,XXXXY Karyotype – A Case Report

Abstract: Background: Epignathus is a rare form of congenital teratoma, originating from the base of the skull, most commonly the hard palate, or mandible. It has been associated with a poor prognosis due to complications including polyhydramnios and respiratory compromise at birth as a consequence of upper airway obstructions. It is usually not associated with chromosomal aberrations. We present a case of prenatally diagnosed epignathus associated with a gonosomal pentasomy 49,XXXXY. Case: A 34-year-old gravida 1, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
(15 reference statements)
0
5
0
12
Order By: Relevance
“…An epignathus is a rare congenital orofacial teratoma. In some studies, epignathi have been found to be associated with chromosomal abnormalities, such as duplication of 1q and 19p [8], ring X chromosome mosaicism [9], and the 49,XXXXY karyotype [10]. However, other studies have reported epignathi with no chromosomal abnormalities [11, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An epignathus is a rare congenital orofacial teratoma. In some studies, epignathi have been found to be associated with chromosomal abnormalities, such as duplication of 1q and 19p [8], ring X chromosome mosaicism [9], and the 49,XXXXY karyotype [10]. However, other studies have reported epignathi with no chromosomal abnormalities [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…1330 g3.5 cm in diameter, oral tumor attached to the hard palate in the midline, tridermaltumor was in continuity, via a narrow defect in the hard palate, sphenoid bone, third ventricle, extending to the lateral ventriclescentral tumour mass separating the temporal lobes, which progected rostrally between dilated lateral ventricles, partly replacing the septum pellucidumSmith [15]199328 y-o., para 1, polyhydroamnion18 fetal w., aborted., f.2 cm in diameter, slightly gelatinous nodule protruding ftom the right upper lip and attached to the right maxilla, tridermalnarrow cord which traversed the nasal bones and entered the cranial cavity in the region of the pituitary fossa and direct communication with the mass in the frontal lobes.partly cystic, lobular mass replacing the frontal. Predominantly neuroglial, with prominent ependymal rosettesJohnston [10]2007no information38 fetal w., m.,4 × 5 cm, midline oropharyngeal mass protruding through a cleft deformitynoneanterior and middle cranial fossaeCalda [17]201029 y-o., primigravida20 fetal w., aborted., f., B.W. 310 g2 cm in diameter, lobulated round vascular mass, visible trhough the open oral cavity, tridermalnone13x10x7 mm, neuroepithelial intracranial cystWang [12]201731 y-o., primagravida17 fetal w., aborted, m., 355 g6.7 × 6.5 × 5.0 cm, protruding from the right maxillofacial region, tridermaldirectly growing upwardmiddle and posterior cranial fossa, 3.5 cm in diameter, tridermalOur case201832 y-o., 3 gravida para 227 fetal w., stillborn, f., 1228 g12x6x6 cm, 270 g, solid and multicystic tumor, based on the soft palate and protruding from mouththe right side of the sella turcica, 2 mm in diametermiddle cranial fossa, capsuled tumor, 24 g, no direct invasion to the brain…”
Section: Discussionmentioning
confidence: 99%
“…El trimestre al momento del diagnóstico, fue de un caso en primer trimestre, realizado en la semana 12 de gestación, representando el 1,8 % de los casos (36). En el segundo trimestre entre las 14-28 semanas fue del 70,9 % de los casos (n = 39) (6)(7)(8)11,12,18,(20)(21)(22)(23)(24)(25)(26)30,(32)(33)(34)(35)38,(40)(41)(42)(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(58)(59)(60)(61)(62)(63)(64) y durante el tercer trimestre después de la semana 29 con un 30 % de los casos (n = 17) (10,17,19,27,2 9,31,37,39,41,46,48,49,51,52,57,65). El diagnóstico prenatal se realizó por ecografía obstétrica en el 67,2 % de los casos (n = 37) (6,8,(10)(11)(12)…”
Section: Resultsunclassified
“…SCTs are not usually associated with chromosomal abnormalities. However, cases related to chromosomal abnormalities have also been described ( 18 , 19 , 20 , 21 ) , although this coexistence may be incidental. A previous report described tethered spinal cord associated with SCT ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%